2005
DOI: 10.1086/498501
|View full text |Cite
|
Sign up to set email alerts
|

HST Imaging of MEGA Microlensing Candidates in M31

Abstract: We investigate HST/ACS and WFPC2 images at the positions of five candidate microlensing events from a large survey of variability in M31 (MEGA). Three closely match unresolved sources, and two produce only flux upper limits. All are confined to regions of the color-magnitude diagram where stellar variability is unlikely to be easily confused with microlensing. Red variable stars cannot explain these events (although background supernovae are possible for two). If these lenses arise in M31's halo, they are due … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…Knowledge of the total mass of M31 is vital for the interpretation of the latest generation of pixel microlensing experiments, which concentrate on that galaxy (Crotts 1992; Kerins et al 2001, 2003; Riffeser et al 2003; de Jong et al 2004; Belokurov et al 2005; Cseresnjes et al 2005). Evans & Wilkinson (2000) have found that there is no kinematic evidence to support the widely held belief that M31 is more massive than the Milky Way, in contradiction to previous studies.…”
Section: Introductioncontrasting
confidence: 99%
“…Knowledge of the total mass of M31 is vital for the interpretation of the latest generation of pixel microlensing experiments, which concentrate on that galaxy (Crotts 1992; Kerins et al 2001, 2003; Riffeser et al 2003; de Jong et al 2004; Belokurov et al 2005; Cseresnjes et al 2005). Evans & Wilkinson (2000) have found that there is no kinematic evidence to support the widely held belief that M31 is more massive than the Milky Way, in contradiction to previous studies.…”
Section: Introductioncontrasting
confidence: 99%
“…Its short duration, good sampling and probed achromaticity make of it a robust microlensing event. Furthermore, the possible source has been identified on some HST frame (this identification, however, has been challenged by Cseresnjes et al [96]). PA-N2 [45]/MEGA-ML7 [38], Fig.…”
Section: The Microlensing Candidate Eventsmentioning
confidence: 99%
“…With the source magnitude and color fixed thanks to an analysis of archival Hubble Space Telescope (HST) data, and based on a specific Monte Carlo simulation of the experiment, where the observed characteristics of the event had been used to delimit the possible parameter space (using in particular a lower limit for the lens proper motion), Aurière et al (2001) conclude that the PA-N1 lens is more likely a MACHO if the mass halo fraction in the form of compact halo object is above 20%. The results of this analysis have been however challenged by the MEGA collaboration (who also reported this event as MEGA-ML16, de Jong et al 2006), in particular by Cseresnjes et al (2005) who argued, on the basis of new HST observations, against the source identification reported in Aurière et al (2001).…”
Section: Introductionmentioning
confidence: 98%